A PHARMACOLOGICAL STUDY ON THE ANTI-INFLAMMATORY EFFECTS OF CALENDULA OFFICINALIS EXTRACT ON EXPERIMENTAL ANIMALS - Kumar, Ranjeet; Zilate, Sarju R; Varma, Sushil; Kumari, Sweety (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: Calendula officinalis is one of those plants which have medicinal importance due to its flowers has pharmacological activity the important pharmacological parameters have been less investigated properly and can be scientifically proved by reverse pharmacology. It was found of interest to evaluate these properties of extract of flowers of Calendula officinalis scientifically in experimental models.Methods: Study was conducted in Albino Wistar rats.Fresh Calendula officinalis flowers were collected, extraction and drug formulation was made. Anti-inflammatory activity of hydroalcoholic extract of Calendula officinalis (HECO) flowers was studied in the Carrageenan induced paw edema model & Cotton pellet induced granuloma models The differences between experimental groups were compared by ANOVA followed by Students “t” unpaired test.Results: The Calendula officinalis extract of flowers at 200 and 400 mg/kg showed significant and highly significant inhibition (p< 0.05 and p<0.001, respectively) of paw edema after giving the carrageenan in the rat paw in comparison of control. In cotton pellets induced granuloma pouch method also, the Hydrochloric extract of Calendula officinalis (HECO) flowers  showed very significant reduction of weight of granuloma (p<0.01) with 22.80% protection as compared with control.Conclusion: We conclude that the Anti-inflammatory activity was noted with Hydrochloric extract of Calendula officinalis in a dose-dependent manner in acute (carrageenan-induced hind paw edema model) as well as sub-acute (cotton pellet induced granuloma model) inflammatory experimental models. They decrease the chemical mediators of inflammationKey Words: Calendula Officinalis, anti inflammation, Paw Edema Model, granuloma pouch method , HECO